Delta Cell Hyperplasia in Adult Goto-Kakizaki (GK/MolTac) Diabetic Rats - Lukáš Alán; Tomáš Olejár; Monika Cahová; Jaroslav Zelenka; Zuzana Berková; Magdalena Smětáková; František Saudek; Radoslav Matěj; Petr Ježek (Journal of Diabetes Research)
Reduced beta cell mass in pancreatic islets (PI) of Goto-Kakizaki (GK) rats is frequently observed in this diabetic model, but knowledge on delta cells is scarce. Aiming to compare delta cell physiology/pathology of GK to Wistar rats, we found that delta cell number increased over time as did somatostatin mRNA and delta cells distribution in PI is different in GK rats. Subtle changes in 6-week-old GK rats were found. With maturation and aging of GK rats, disturbed cytoarchitecture occurred with irregular beta cells accompanied by delta cell hyperplasia and loss of pancreatic polypeptide (PPY) positivity. Unlike the constant glucose-stimulation index for insulin PI release in Wistar rats, this index declined with GK age, whereas for somatostatin it increased with age. A decrease of GK rat PPY serum levels was found. GK rat body weight decreased with increasing hyperglycemia. Somatostatin analog octreotide completely blocked insulin secretion, impaired proliferation at low autocrine insulin, and decreased PPY secretion and mitochondrial DNA in INS-1E cells. In conclusion, in GK rats PI, significant local delta cell hyperplasia and suspected paracrine effect of somatostatin diminish beta cell viability and contribute to the deterioration of beta cell mass. Altered PPY-secreting cells distribution amends another component of GK PI’s pathophysiology.